A molecular phylogeny of the extinct South American gomphothere through collagen sequence analysis. (15th November 2019) - Buckley, Michael; Recabarren, Omar P.; Lawless, Craig; García, Nuria; Pino, Mario
Abstract: The extant elephants are only a small fraction of the diverse order of proboscideans that once roamed the planet, whereas the extinct gomphotheres represent the largest and most diverse of these enigmatic groups that survived into the Quaternary. However, their relationship to the living elephantids and the other extinct elephantiformes, such as the mastodons, remains debated. To begin to address this we have used proteomic analysis to sequence the collagen surviving in sub-fossil Notiomastodon bone from the site of Pilauco in Chile. Through the genus-level information retrieved, phylogenetic analyses of the near-complete (85–90%) sequences that were recovered surprisingly revealed a closer relationship between the South American gomphothere ( Notiomastodon ) and the American mastodon ( Mammut ) than to the elephantids ( Loxodonta, Elephas and Mammuthus ), as most commonly proposed; a finding that was consistent across all phylogenetic analyses used, including bayesian, parsimony and máximum likelihood approaches. These results demonstrate the potential information that can be recovered using the ever-increasing applications of proteomics to palaeobiology, particularly for improving our understanding of the evolution of extinct species in a manner consistent with the latest DNA-based approaches. Highlights: Bone collagen sequenced from South American gomphothere Notiomastodon . Molecular phylogeny indicates closer relationship between the South American gomphothere and the American mastodon. Genus-level resolution of collagen sequences provide technique for objective species identification of sub-fossil remains.